ANALISIS YURIDIS TERHADAP PEMBERIAN IZIN POLIGAMI OLEH PENGADILAN (PUTUSAN NOMOR 0743/PDT.G/2018/PA.LMG) - Febrina Puspito Ningtyas; Khairani Bakri (Fakultas Hukum Universitas Trisakti, 2022)
In Indonesia today, polygamy, or the union of one man with the status of a husband and multiple women with the status of wives concurrently, still frequently leads to issues. For instance, consider the incident that took place in Lamongan a while back, where the man (the applicant) was forced to marry the second wife. If it wasn't for him, she didn't want to get married. This condition was later legally granted through the Lamongan Religious Court Decision Number 0743/Pdt.G/2018/PA.Lmg. However, it becomes apparent from various angles that a number of legislative requirements have not been met. utilizing secondary sources and descriptive analytical research techniques. The outcomes of the Research, analysis, and findings demonstrate that the pertinent decisions are compliant with the law. Simply put, the applicant's arguments do not follow Law Number 1 of 1974's provisions for Article 4 Paragraph 2 Jo, Government Regulation Number 9 of 1975's provisions for Article 41 letter a Jo, or List of Compilation or Association of Islamic Laws Article 57. Specifically, polygamy is only permitted if the wife is unable to fulfill her commitments, suffers from a handicap or disease, and is sterile.